PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI SATUAN PANJANG MELALUI MEDIA FLASH CARD PADA SISWA KELAS IIB SDN KAYURINGIN JAYA VI BEKASI - Mutia Intan Rizkyani; Winda Amelia (Universitas Trilogi, 2020)
This class action research was carried out with the aim to improve student learning outcomes of Class IIB Kayuringin Jaya VI SDN Bekasi in long unit material mathematics through the use of flash card media. The research data were obtained from observations, interviews and student learning outcomes. The results showed that there was an increase in student learning outcomes through the use of flash card media in long term material mathematics subjects. In cycle 1, the percentage of classical learning completeness is 57% with a classical average value of 75.9. In cycle II, the percentage of classical learning completeness experienced a significant increase of 90% with a classical average value of 83.8. This shows that there is an increase in the percentage of classical completeness by 33% and an increase in the classical average value of 7.9. So, it can be concluded that the use of flash card media can improve the learning outcomes of students in class IIB SDN Kayuringin Jaya VI Bekasi in long unit material mathematics.